Disease recurrence after lung transplantation for idiopathic pulmonary hemosiderosis. (2020) - Ross, Bryan; Halloran, Kieran; Adam, Benjamin; Laing, Bryce; Hirji, Alim
Abstract: Idiopathic pulmonary hemosiderosis is characterized by the triad of hemoptysis, iron deficiency anemia and pulmonary infiltrates. Though idiopathic pulmonary hemosiderosis has classically been described as a childhood disease, survival into adulthood is possible. Treatment options for advanced and/or refractory disease is limited, and in our unique case of idiopathic pulmonary hemosiderosis with precapillary pulmonary hypertension, lung transplantation has had a favorable short-term outcome. We also demonstrate that disease recurrence of idiopathic pulmonary hemosiderosis following lung transplantation is possible.